Left atrial strain predicts the rhythm outcome in patients with persistent atrial fibrillation undergoing left atrial cryoablation during minimally invasive mitral valve repair - Yildirim, Yalin; Yildirim, Sevenai; Petersen, Johannes; Alassar, Yousuf; Sarwari, Harun; Sinning, Christoph; Blankenberg, Stefan; Reichenspurner, Hermann; Pecha, Simon (Frontiers in Cardiovascular Medicine, 2024)
Left-atrial (LA) strain is a predictor for left-atrial function and is reduced in patients with atrial fibrillation. We here evaluated the prognostic value of LA strain to predict rhythm outcome in patients with persistent AF undergoing left-atrial cryoablation concomitant to minimally invasive mitral valve repair.Between 01/2016 and 12/2020, 72 patients with persistent AF underwent left-atrial cryoablation during minimally invasive mitral valve surgery. All patients received a complete left-atrial lesion set and LAA closure with a clip. All patients received a preoperative TTE with left-atrialand left-ventricular strain measurement. Preoperative LA-and LV Strain analysis was correlated with postoperative rhythm outcome.Mean patients age was 66.9±7.2 years, 42 (58%) were male patients. No major ablation related complications occurred in any of the patients. Successful LAA closure was confirmed by intraoperative echocardiography in all patients. One-year survival rate was 97%. Freedom from AF at 12 months was 72% and 68% off antiarrhythmic drugs. Preoperative LA-strain values were statistically significant higher in patients with freedom from AF at 12 months' follow-up (12.7%±6.9% vs. 4.9%±4.1%, p=0.006). Preoperative LV-Strain value was not associated with postoperative rhythm outcome. In multivariate logistic regression analysis, LA Strain (p<0.001) and AF duration (p= 0.017) were predictors for freedom from AF at 12 months follow-up.In our study, LA strain analysis predicted rhythm outcome in patients with persistent atrial fibrillation undergoing concomitant surgical AF ablation. In future, LA strain might be a useful tool to guide decision making on ablation strategies in patients with persistent atrial fibrillation.